2018
DOI: 10.1002/adsc.201800561
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom Donor‐Decorated Polymer‐Immobilized Ionic Liquid Stabilized Palladium Nanoparticles: Efficient Catalysts for Room‐Temperature Suzuki‐Miyaura Cross‐Coupling in Aqueous Media

Abstract: Palladium nanoparticles stabilized by heteroatom donor-modified polystyrene-based polymer immobilized ionic liquids (PdNP@HAD-PIILP; HAD-PPh 2 , OMe, NH 2 , CN, pyrrolidone) are highly efficient catalysts for the Suzuki-Miyaura cross-coupling in aqueous media under mild conditions. Catalyst modified with phosphine was consistently the most efficient as it gave high yields across a range of substrates under mild conditions at low catalyst loadings. Incorporation of polyethylene glycol into the phosphine modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 192 publications
0
38
0
Order By: Relevance
“…We also compared the TOF value of Pd-PPQ with other existing heterogeneous catalysts reported in literatures. [35][36][37][38][39][40][41][42][43][44][45] Entry 1 ( Table 2) was used as an example and the comparison was summarized in Figure 4a. We concluded that Pd-PPQ reached unprecedented catalytic efficiency compared to literature reports!…”
Section: Resultsmentioning
confidence: 99%
“…We also compared the TOF value of Pd-PPQ with other existing heterogeneous catalysts reported in literatures. [35][36][37][38][39][40][41][42][43][44][45] Entry 1 ( Table 2) was used as an example and the comparison was summarized in Figure 4a. We concluded that Pd-PPQ reached unprecedented catalytic efficiency compared to literature reports!…”
Section: Resultsmentioning
confidence: 99%
“…55 However, heterocycles are likely to coordinate with transition metals, thus representing a challenging class of starting materials for metal-catalyzed reactions with low catalyst dosages. 56 With this method, a variety of heterocyclic compounds including pyridine (24)(25)(26)(27)(28), quinoline (29), carbazole (27), dibenzofuran (28), indole (30), pyrimidine (31-32), pyrazine (33), pyrazole (34), imidazo[1,2-a]pyrazine (35), thiophene (36)(37)(38)(39)(40), benzothiophene (41), and furan (42), could be used to generate corresponding products, representing the broadest substrate scope obtained with a polymeric catalyst as far as is known.…”
Section: Resultsmentioning
confidence: 99%
“…12,22,23 Based on previous achievements of using electron-rich phosphine ligands to promote SM couplings, [24][25][26][27][28][29][30][31] Carrow and co-workers revealed that a tri(adamantyl)phosphine-Pd complex catalyzed a process with low Pd loadings in an organic solvent. 13 Whereas polymeric materials loaded with Pd are easily recyclable for homo/heterogeneous SM couplings, [32][33][34][35][36][37][38][39][40][41][42] in comparison to small molecule catalysts, polymeric catalysts generally exhibit: (a) limited functional group tolerance, (b) decreased reactivity toward deactivated aryl chlorides, and (c) unsatisfactory compatibility with heterocycles. 43 Furthermore, tandem/ iterative catalysis based on chemoselective SM coupling [44][45][46] has rarely been realized with polymeric catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…At the optimal reaction condition, i.e. 6 hours heating at 100 C, the % yield of the cross-coupling product was monitored by GC-MS which displayed in percentages amount of the C-C product under the same sustainable conditions (50,49,61 and 39%, respectively), as shown in Table 9. Potassium carbonate is the most favored base for the C-C catalytic process, due to the strong interaction between the catalyst, solvent (H 2 O) and the base to enhance the catalytic potential.…”
Section: Stability and Thermodynamic Propertiesmentioning
confidence: 99%
“…46 Sustainably, the incorporated sodium sulfonate group to the synthesized Schiff base ligand improves its reactivity and the corresponding metal complexes under green conditions. 41 Ionic liquids, as imidazolium-and pyridinium-based liquids are of interest as solvents [47][48][49][50] or co-catalysts 51-54 for many C-C biaryls syntheses, e.g. Suzuki-Miyaura cross-coupling protocols.…”
Section: Introductionmentioning
confidence: 99%